Do associations of sex, age and education with transport and leisure-time physical activity differ across 17 cities in 12 countries? - Mitáš, Josef; Cerin, Ester; Reis, Rodrigo Siqueira; Conway, Terry L; Cain, Kelli L; Adams, Marc A; Schofield, Grant; Sarmiento, Olga L; Christiansen, Lars B; Davey, Rachel; Salvo, Deborah; Orzanco-Garralda, Rosario; et al. (The international journal of behavioral nutrition and physical activity, 2019)
BACKGROUND: Leisure-time and transport activity domains are studied most often because they are considered more amenable to intervention, but to date evidence on these domains is limited. The aim of the present study was to examine patterns of socio-demographic correlates of adults' leisure-time and transport physical activity and how these associations varied across 17 cities in 12 countries. METHODS: Participants (N = 13,745) aged 18-66 years in the IPEN Adult study and with complete data on socio-demographic and self-reported physical activity characteristics were included. Participants reported frequency and duration of leisure-time and transport activities in the last 7 days using the self-administered International Physical Activity Questionnaire-Long Form. Six physical activity outcomes were examined in relation with age, education, and sex, and analyses explored variations by city and curvilinear associations. RESULTS: Sex had the most consistent results, with five of six physical activity outcomes showing females were less active than males. Age had the most complex associations with self-report transport and leisure-time physical activity. Compared to older people, younger adults were less likely to engage in transport physical activity, but among those who did, younger people were likely to engage in more active minutes. Curvilinear associations were found between age and all three leisure-time physical activity outcomes, with the youngest and the oldest being more active. Positive associations with education were found for leisure-time physical activity only. There were significant interactions of city with sex and education for multiple physical activity outcomes. CONCLUSIONS: Although socio-demographic correlates of physical activity are widely studied, the present results provide new information. City-specific findings suggest there will be value in conducting more detailed case studies. The curvilinear associations of age with leisure-time physical activity as well as significant interactions of leisure-time activity with sex and education should be further investigated. The findings of lower leisure-time physical activity among females as well as people with low education suggest that greater and continued efforts in physical activity policies and programs tailored to these high-risk groups are needed internationally.
Keywords: volnočasové aktivity; mužské pohlaví; Male; senioři; Health disparities; Humans; Female; stupeň vzdělání; Social epidemiology; IPAQ; lidé; Middle Aged; ženské pohlaví; cvičení; lidé středního věku; International health; mladiství; Educational Status; Young Adult; Adolescent; mladý dospělý; Exercise; Physical activity domain; Leisure Activities; dospělí; Adult; Aged